Development of an H2S emission model for wastewater treatment plants. (3rd October 2021) - Tian, Lan; Han, Caiyun; Zhang, Jingyu; Ouyang, Yun; Xi, Jinying
ABSTRACT: Modeling and prediction of H2 S emission from wastewater are important since gaseous H2 S will induce significant corrosion and odor problems. Most previous studies focused on H2 S emission of wastewater in pipeline systems, which may not be fit for H2 S emission in wastewater treatment plants (WWTPs). This study provided a two-phase mass transfer model for prediction of H2 S emission concentrations. The model is based on the mass transfer rate equation of the mass transfer impetus, expressed by the concentration difference. The main parameters of the model are the mass transfer coefficient, the carrier gas flow rate and the concentration of H2 S in liquid phase. The results showed that the model can simulate and predict H2 S emission concentrations of various processes in WWTPs. Moreover, the model can analyze and predict the influences of different pH values, mass transfer coefficients and carrier gas flow rates on H2 S emission concentrations and loads. Therefore, the model provides theoretical guidance for design of WWTPs regarding H2 S emissions. Implications : Modeling and prediction of H2 S emission from wastewater are quite important since gaseous H2 S will induce significant corrosion and odor problems. Most of previous studies are focused on H2 S emission from wastewater in pipeline system, which may not be fit for H2 S emission in wastewater treatment plants (WWTPs). Thus in this study, a model for predicting H2 S emission from typical units of WWTPs is established and verified. Moreover, the influences of pH values, mass transfer coefficients and carrier gas flow rates on H2 S emission are analyzed. The model can be a useful tool to predict the H2 S concentration in odor gas collection system of WWTP and understand the behaviors of H2 S emission under different WWTPs operating conditions.